Discontinuation rate and reason for discontinuation after sodium‐glucose cotransporter 2 inhibitor prescription in real clinical practice. (13th June 2020) - Kim, Hyunah; Lee, Seung‐Hwan; Cho, Jae‐Hyoung; Lee, Hyunyong; Yim, Hyeon Woo; Yoon, Kun‐Ho; Kim, Hun‐Sung
Abstract: What is known and objectives: Sodium‐glucose cotransporter 2 inhibitors (SGLT2i) are novel antidiabetic agents that have advantages of weight loss and prevention of cardiovascular diseases. However, SGLT2i have various side effects. To understand their effectiveness, we analysed patients who had discontinued the use of dapagliflozin, an SGLT2i, 3 months after the initial prescription. We evaluated the discontinuation rate of dapagliflozin and the incidence rate of its side effects. Methods: Patients who were initially prescribed dapagliflozin for blood sugar control from December 2014 to December 2016 were analysed. Data of patients in whom dapagliflozin administration was discontinued 90 days after initial prescription were collected separately, and the reasons were evaluated by a direct chart review. Results and discussion: A total of 8.96% (149/1663) patients discontinued dapagliflozin or switched medications within 3 months. Dapagliflozin was discontinued in 24.8% (37/149) of cases due to unexpected causes such as increased blood sugar and weight gain. The patients who discontinued dapagliflozin use due to side effects comprised 49.7% (74/149). Two major side effects were genital tract infection in women ( P < .001 compared with men) and urinary tract infection, which increased with age ( P = .030). Malpractice of medical personnel, insurance problems or causes of termination not related to dapagliflozin use comprised 14.1% (21/149). What is new and conclusion: The incidence of side effects with dapagliflozin was not as high as expected. Physicians should consider instructions prior to prescribing dapagliflozin so that its discontinuation would decrease considerably. Abstract : SGLT2i have advantages of weight loss and prevention of cardiovascular diseases. The incidence of side effects with dapagliflozin was not as high as expected. Physicians should consider instructions prior to prescribing dapagliflozin.